Olhares sobre a presença masculina num grupo de convivência - Vargas, Alessandra Cardoso (2012)
In this dissertation, a social group from a rural location is analyzed, where male participation is distinguished from others. The goal of the present work is to identify the determinants of male participation in the social group from the Farinhas location, in the city of Alpestre (RS), and the meaning in their lives. With this purpose, a qualitative descriptive/exploratory study was performed. Semi structured interviews were carried for data collection, they were also recorded, transcribed, and later rerecorded, with 71 participants of the social group from the Farinhas location, in the city of Alpestre, Rio Grande do Sul, where 36 were male and 35 female with ages from 50 to 90 years old. From the theme analysis of the speeches of respondents, it was verified the meaning of the group in their lives, where they had an improvement of group experience, cooperation, fun, change of habits, new friendships, overcoming of losses, among other factors which directly influenced their self-esteem and social welfare. It is noted that the participants seek a new sense to their existence when joining the group. With this new vision, that once generalized passive being no longer exists simply for having experienced many decades, providing these people who participate in these social programs the possibility of self-realization and the achievement of a better quality of life. Thus, it is proved that the search for groups is crescent and spontaneous, which shows that the population of this age group are aware that they will be living longer, so they seek to redesign their lifestyle building ways to stay healthy, active, and independent enough to enjoy the extra years that life reserves for them. Finally, the choices of changing their lifestyle awaken in the human being the importance of respecting their desires and values to a successful and healthy aging.